Correction of nasal defect after cheiloplasty: a case report - Raúl Rivera Truyt (Acta Médica del Centro, 2012)
The treatment of nasal deformity associated with unilateral cleft lip, alveolus and palate is one of the most difficult aspects in the therapeutics of these birth defects. The case of a male patient suffering from a non-syndromic cleft lip, alveolus and palate classified as a trans-foramen incisor cleft or right unilateral complete cleft lip, alveolus and palate is reported.